Expression of Humanity and Love in the Novels of Utkir Hashimov (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2024)
Utkir Hashimov is one of the brightest representatives of Uzbek literature, in whose works the themes of the inner world of man, moral values, and love occupy a special place. This article analyzes the issues of humanity, love, and hymns in the works of Utkir Hashimov. The writer's novels and stories reflect not only the individual, but also the moral and spiritual image of society. The article discusses the human feelings expressed in the works, the importance of love and its role in society, as well as Hashimov's literary style and the philosophical content of the works. Studying the works of Utkir Hashimov helps to discover new approaches to depicting humanity and love in modern literature.